A STUDY ON LOCAL AND REGIONAL JOURNALISM IN BRAZIL: a survey of theses and dissertations (2010-2020) - Assunção Reis, Thays (Brazilian journalism research, 2022)
ABSTRACT – This article aims to provide an overview of local and regional journalism research in Brazil. To do this, we conducted a survey of theses and dissertations on local and/or regional journalism defended in postgraduate communication and journalism between 2010 and 2020. The data was collected from the Capes Catalog and the Brazilian Digital Library of Theses and Dissertations (BDTD) and then analyzed for content analysis and bibliometrics. We identified and analyzed a total of 115 academic writings, comprising 102 dissertations and 13 theses. Our results showed a predominance of regional studies, a concentration of empirical studies in state capitals and cities, and a presence of “research deserts” in the country. RESUMO – Este artigo tem por objetivo traçar um panorama das pesquisas de jornalismo local e regional no Brasil. Para isso, realizamos um levantamento das teses e dissertações sobre jornalismo local e/ou regional defendidas em programas de pós-graduação em comunicação e jornalismo entre os anos de 2010 e 2020. Os dados foram coletados no Catálogo da Capes e na Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) e analisados a partir dos parâmetros da análise de conteúdo e da bibliometria. Ao todo, identificamos e analisamos 115 produções, sendo 102 dissertações e 13 teses. Entre os resultados obtidos destaca-se a predominância de pesquisas classificadas tematicamente como regionais, a concentração dos estudos empíricos nas capitais estaduais e metrópoles e a presença de “desertos de pesquisa” no país. RESUMEN – Este artículo tiene como objetivo proporcionar una visión general de la investigación periodística local y regional en Brasil. Para ello, realizamos un relevamiento de tesis y disertaciones sobre periodismo local y/o regional defendidas en programas de posgrado en comunicación y periodismo entre 2010 y 2020. Los datos fueron recolectados en el Catálogo Capes y en la Biblioteca Digital Brasileña de Tesis y Disertaciones (BDTD) y analizados desde los parámetros de análisis de contenido y bibliometría. En total, identificamos y analizamos 115 producciones, de las cuales 102 fueron disertaciones y 13 tesis. Entre los resultados obtenidos, se destacan el predominio de investigaciones clasificadas temáticamente como regionales, la concentración de estudios empíricos en capitales de estado y metrópolis y la presencia de “desiertos de investigación” en el país.